2015
DOI: 10.1002/hep.28111
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine prevents hepatitis C virus membrane fusion in a genotype‐dependent manner by targeting the potential fusion peptide within E1

Abstract: To explore mechanisms of hepatitis C virus (HCV) replication we screened a compound library including licensed drugs. Flunarizine, a diphenylmethylpiperazine used to treat migraine, inhibited HCV cell entry in vitro and in vivo in a genotype-dependent fashion. Analysis of mosaic viruses between susceptible and resistant strains revealed that E1 and E2 glycoproteins confer susceptibility to flunarizine. Time of addition experiments and single particle tracking of HCV demonstrated that flunarizine specifically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
92
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 35 publications
4
92
1
Order By: Relevance
“…In fact, administration of flunarizine only during a 5-min-long wash with low-pH buffer was necessary and sufficient to inhibit HCV infection (7). Moreover, using singleparticle-tracking live-cell imaging, we observed that, in the presence of flunarizine, HCV particles readily reached cellular tight junctions and were internalized into endosomes but that only membrane fusion was inhibited (7). Since viral flunarizine resistance mutations, which map to residues M267 and Q289 of E1 and M405 of E2 (J6 isolate, GT2a), confer cross-resistance to pimozide, fluphenazine, and trifluoperazine, it can be assumed that these related diphenyl-piperidines and phenothiazines share a mode of action, which, given the findings described above, is unlikely to be inhibition of endocytosis (7).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, administration of flunarizine only during a 5-min-long wash with low-pH buffer was necessary and sufficient to inhibit HCV infection (7). Moreover, using singleparticle-tracking live-cell imaging, we observed that, in the presence of flunarizine, HCV particles readily reached cellular tight junctions and were internalized into endosomes but that only membrane fusion was inhibited (7). Since viral flunarizine resistance mutations, which map to residues M267 and Q289 of E1 and M405 of E2 (J6 isolate, GT2a), confer cross-resistance to pimozide, fluphenazine, and trifluoperazine, it can be assumed that these related diphenyl-piperidines and phenothiazines share a mode of action, which, given the findings described above, is unlikely to be inhibition of endocytosis (7).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
“…Moreover, pimozide inhibits T-type Ca 2ϩ channels much more effectively than flunarizine (38) but inhibits HCV about as much as flunarizine (7). Beyond this, other potent Ca 2ϩ channel inhibitors, like mibefradil (41), penfluridol (42), and NiCl 2 (43), do not inhibit HCV, and chelation of intracellular or extracellular Ca 2ϩ does not influence the antiviral activity of flunarizine (7). Taken together, these observations indicate that the anti-HCV activities of chlorcyclizine and flunarizine (and likely also of compounds related to these molecules) are independent of the inhibition of H 1 histamine receptors, dopamine receptors, and Ca 2ϩ ion channels.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 3 more Smart Citations